Potret Lembaga Tahfiz Al-Qur'an di Indonesia: Studi Tradisi Pembelajaran Tahfiz - Muhammad Syatibi AH (SUHUF, 2008)
Generally, the model of the institution for memorizing the Qur'an (learning the Qur'an by heart) in Indonesia is the institute for specializing the Qur'an which is held by the family, one of the units in the institute of the Islamic boarding school (pesantren); and special institute which is held by the Islamic foundation. The chains of the memorization (sanad tahfiz) are dominated by five Islamic scholars having studied in Saudi Arabia. They are KH M Munawwir of Krapyak; KH M Munawwir of Sidayu Gresik; KH M Said bin Ismail of Sampang Madura, KH M Mahfuz at-Tarmasi of Pacitan, and KH M Dahlan Khalil of Jombang